Productivity convergence and divergence in Latin America, 1970-2014 - Chrēstos Kollias; Panayiotis Tzeremes; Nickolaos G. Tzeremes (Review of Economic Analysis (REA), 2021)
The paper examines Latin American countries' productivity growth levels and their convergence patterns utilizing nonparametric frontier approaches. Utilizing a sample of 17 Latin American countries for the period 1970-2014 it estimates various productivity indexes alongside with their main components. Moreover a convergence analysis is conducted estimating relative productivity convergence paths. The results suggest that over the period examined, countries' productivity growth levels have contracted. We provide evidence that the implementation of the structural reforms of the 1990s do not appear to have driven Latin American countries to higher productivity levels. Moreover, the results do not render support to the productivity convergence hypothesis. On the other hand, some support was found for countries' technological change levels, identifying three convergence clubs.
Keywords: O40; O47; O54; 330; Productivity convergence; Latin American countries; Nonparametric analysis